The taxation of the returns on debt and equity in South Africa - Wortmann, Neil (My University, 2016)
The existing South African tax system only acknowledges debt financing through the deduction allowed for interest payments, as compared to equity financing where no such deduction is allowed for dividend payments. Taxpayers are prejudiced should they wish to use equity financing to fund a project or company. The deductibility of interest creates the incentive for taxpayers to use debt funding even when it may not be in the best interests of the company. This paper considers some of the complications of the different tax treatment of the returns on debt and equity. Alternative models including the comprehensive business income tax, an allowance for corporate equity and a deduction for dividends are considered in order to establish whether the taxation of the returns on debt and equity could be improved or simplified in South Africa. Key Words: debt, equity, hybrid instruments, tax deductibility, comprehensive business income tax, allowance for corporate equity, dividend deductibility, South Africa
A research report submitted to the Faculty of Commerce, Law and Management in partial fulfillment of the requirements for the degree of Master of Commerce (specialising in Taxation). Johannesburg, 2015
Keywords: Debt; Equity; Hybrid instruments; Tax deductibility; Dividend deductibility; South Africa